Going underground : the meanings of death and burial for minority groups in Israel - Shay, Talia, (Archaeopress Archaeology, 2021)
This volume is about the attitudes towards death and burial in contemporary society. It provides information on the attitudes of several minority groups living in Israel today, including four communities of Russian Jews, an ultra-religious Jewish community and a Palestinian-Christian community.